2016
DOI: 10.1002/cite.201600028
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of Nano‐Calcium Carbonate: The Influence of Process Parameters

Abstract: Precipitated calcium carbonate was synthesized by carbonation of calcium hydroxide in the presence and absence of ultrasound (conventional stirring) at atmospheric as well as at elevated pressures and different initial concentrations of Ca(OH) 2 . Spherical morphology of the formed calcite was favored at high Ca(OH) 2 concentrations and low CO 2 pressures. The presence of ultrasound did not show any influence on the reaction rate in case of efficient mixing. A small increase of the reaction rate was observed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Figure 4 showed that thermal decomposition behavior of calcium carbonate was similar. The whole decomposition process was accompanied by three weight loss stages [25]. The first one before 385 ∘ C was associated with the loss of crystal water.…”
Section: Mmt and Carbonate Mineralization Synergisticallymentioning
confidence: 99%
“…Figure 4 showed that thermal decomposition behavior of calcium carbonate was similar. The whole decomposition process was accompanied by three weight loss stages [25]. The first one before 385 ∘ C was associated with the loss of crystal water.…”
Section: Mmt and Carbonate Mineralization Synergisticallymentioning
confidence: 99%
“…The adjustment of process parameters can help prepare different morphologies of CaCO 3. The relationship between process and morphology was established. Mechanism analysis only involves the transport of Ca 2+ and CO 3 2– , which is prone to the analysis of macroscopic forces. However, the interactions between pre-nucleated clusters, primary nanoparticles, or other intermediate states are chiefly controlled by microscopic forces, which can significantly affect crystal morphology and structure .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have evaluated the effect of ultrasonic treatment in the production of different materials with extraordinary properties [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] . Conducting ultrasonic irradiation accelerated the carbonation mechanism resulting in a faster production of PCC particles was determined [23] , [24] , [30] , [31] . During production, formed PCC particles were crushed and the corresponding particle morphology was altered owing to a shaping effect, which led to the formation of spherical particles rather than other crystal shapes [32] .…”
Section: Introductionmentioning
confidence: 99%